Kesalahan dalam Penerjemahan Kalimat Pasif dan Kalimat Kausatif dari Bahasa Indonesia ke Bahasa Jepang: Studi Kasus Pemelajar di Tiga Universitas di Padang - Dewi Kania Izmayanti; Irma Irma; Syahrial Syahrial (Vocational College of Diponegoro University, 2026)
This study aims to analyze errors found in the translation of passive and causative sentences from Indonesian to Japanese by students at three universities in Padang. This study uses a qualitative descriptive method, by analyzing the translation of passive and causative sentences from Indonesian to Japanese written by 66 Japanese Literature students from three universities in Padang. The theory used is the theory of language errors from Pateda, which states that language errors can occur at the phonological, morphological, semantic, and syntactic levels. Errors found in the translation of passive and causative sentences are found in sentence structure, word choice, the use of postpositions and posverbs. In sentence structure, errors are caused by differences in the construction of passive and causative sentences in Indonesian and Japanese. In word choice, errors are caused by Japanese having several words with the same meaning. Errors in the use of postpositions (auxiliary words) and posverbs (auxiliary verbs) occur in their use, which is not in accordance with the structure and rules of Japanese. From the findings obtained, it can be concluded that errors made by Japanese language learners are due to a lack of understanding of translation and the rules in Japanese. This should require more in-depth explanation and practice regarding translation from Indonesian into Japanese.